At return to play following hamstring injury the majority of professional football players have residual isokinetic deficits - Tol, J. L.; Hamilton, B.; Eirale, C.; Muxart, P.; Jacobsen, P.; Whiteley, R. (British Journal of Sports Medicine, 2014)
Background: There is an ongoing debate regarding the optimal criteria for return to sport after an acute hamstring injury. Less than 10% isokinetic strength deficit is generally recommended but this has never been documented in professional football players after rehabilitation. Our aim was to evaluate isokinetic measurements in MRI-positive hamstring injuries.